Food bioactives : functionality and applications in human health - Deka, Sankar Chandra, 1965-; Seth, Dibyakanta, 1980-; Hulle, Nishant Rachayya Swami, 1985- (Oakville, ON ; Palm Bay, Florida : Apple academic Press, 2020)
"Food Bioactives: Functionality and Applications in Human Health helps to address the growing consumer demand for novel functional food products and for high value and nutritionally rich products by focusing on the sources and applications of bioactives from food. The chapters in the book describe functional properties and discuss applications of the selected food ingredients obtained from various sources, including culinary banana, phalsa, pseudocereals, roselle calyces, asparagus, and more. Several chapters address the resurgence of interest in pseudocereals due to their excellent nutritional and biological values, gluten-free composition, and the presence of some health-promoting compounds. The book also looks at utilizing industrial byproducts for making functional and nutraceutical ingredients. The chapters on prebiotics and probiotics highlight different functional properties, and a chapter on food allergens discusses advancements in detection and management in the food manufacturing industries. With contributions from experts in their respective fields, this book provides topics covering selected important areas of food science, technology and processing and their application for developing novel food products"--
OCLC-licensed vendor bibliographic record.
Keywords: Functional foods; Bioactive compounds; Food industry and trade; SCIENCE / General; TECHNOLOGY / Food Science